THN 102 for Excessive Daytime Sleepiness Associated with Parkinson's Disease: A Phase 2a Trial. Issue 2 (28th October 2021) - Corvol, Jean‐Christophe; Azulay, Jean‐Philippe; Bosse, Björn; Dauvilliers, Yves; Defebvre, Luc; Klostermann, Fabian; Kovacs, Norbert; Maltête, David; Ondo, William G.; Pahwa, Rajesh; Rein, Werner; Thobois, Stéphane; et al.
Abstract: Background: Excessive daytime sleepiness (EDS) is a frequent and disabling symptom of Parkinson's disease (PD) without approved treatment. THN102 is a novel combination drug of modafinil and low‐dose flecainide. Objective: The aim of this study is to evaluate the safety and efficacy of THN102 in PD patients with EDS. Methods: The method involved a randomized, double‐blind, placebo‐controlled, crossover trial testing two doses of THN102 (200 mg/d modafinil with 2 mg/d [200/2] or 18 mg/d flecainide [200/18]) versus placebo; 75 patients were exposed to treatment. The primary endpoint was safety. The primary efficacy outcome was the change in Epworth Sleepiness Scale (ESS) score. Results: Both doses of THN102 were well tolerated. ESS significantly improved with THN102 200/2 (least square means vs. placebo [95% confidence interval, CI]: −1.4 [−2.49; −0.31], P = 0.012) but did not change significantly with the 200/18 dosage. Conclusions: THN102 was well tolerated and showed a signal of efficacy at the 200/2 dose, supporting further development for the treatment of EDS in PD. © 2021 International Parkinson and Movement Disorder Society